2021
DOI: 10.24959/ophcj.21.238177
|View full text |Cite
|
Sign up to set email alerts
|

Determination of catechins in green tea leaves by HPLC compared to spectrophotometry

Abstract: Aim. To study the qualitative composition, the quantitative content of catechins in green tea leaves and compare the data obtained with those evaluated by spectrophotometry.Materials and methods. Green tea leaves used for the analysis were collected in Anhui Province, China. The extract for the HPLC analysis was obtained by the maceration method with 60 % ethanol twice in the raw material/extractant ratio of 1 : 20. In the case of the spectrophotometric analysis, green tea leaves were extracted with 70 % ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A potential medicinal plant for averting and managing dental caries is the green tea leaf. In our studies, it was found that green tea leaf is rich in catechins (epigallocatechin3Ogallate, epicatechin, (+)catechin), flavonols (rutin, quercetin), organic (citric, oxalic acid) and phenylcarboxylic acids (gallic, quinic and caffeic acid) [6,7]. The main group of compounds in green tea leaf are catechins that have antioxidant, anti-inflammatory, antimicrobial, and antifungal effects [8,9].…”
Section: Original Researchmentioning
confidence: 87%
“…A potential medicinal plant for averting and managing dental caries is the green tea leaf. In our studies, it was found that green tea leaf is rich in catechins (epigallocatechin3Ogallate, epicatechin, (+)catechin), flavonols (rutin, quercetin), organic (citric, oxalic acid) and phenylcarboxylic acids (gallic, quinic and caffeic acid) [6,7]. The main group of compounds in green tea leaf are catechins that have antioxidant, anti-inflammatory, antimicrobial, and antifungal effects [8,9].…”
Section: Original Researchmentioning
confidence: 87%
“…Vanillin reagent assay was then applied to determine total catechins [11]. The absorbance was measured at 505 nm.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Green tea leaves are the major source of catechins. The content of catechins there varies from 25 to 35 % [5]. Moreover, green tea leaves contain other subgroups of phenolic compounds.…”
Section: •-mentioning
confidence: 99%
“…where С x -is the concentration of gallic acid according to the calibration curve, С × 10 -6 , g mL -1 ; V -is the volume of the extract, mL; K dil -is the dilution coefficient. The vanillin reagent assay was applied to determine the total amount of catechins [5], and the absorbance was measured at 505 nm. The calibration curve was plotted within interval concentrations of (100 -400) × 10 -6 g mL -1 , the calibration equation Y = 0.0025X -0.0851 (R 2 = 0.9951).…”
Section: Preparation Of the Standard Solutionsmentioning
confidence: 99%